The road to equality? EU diffusion of anti-discrimination norms in Armenia. Issue 3 (3rd April 2022) - Delcour, Laure
ABSTRACT: The EU's diffusion of its norms lie at the core of its neighbourhood policy. However, while scholars have uncovered selective patterns of EU norm adoption and application, still little is known about what shapes the resonance of EU norms in the partner countries. This question matters for the EU's proclaimed objective of transforming its neighbours, in a region fraught with a competition of soft influences between the EU and Russia. In order to cast light on local resonance of external norms, the article delves into identification processes within the partner countries in relation to the values promoted by the EU and Russia. Focusing on an idiographic case study, it examines how the EU's diffusion of anti-discrimination has hit home in Armenia, in a context marked by Russia's staunch defense of "traditional values". The research relies on semi-structured interviews and elites' discourses, which are analysed using frame analysis. It highlights a shift from discursive rejection of the EU's normative script to tentative discursive acceptance – at least at elite level – after the Velvet revolution. The article shows how the diffusion of external values feeds into domestic dynamics and illuminates the role of domestic elites in filtering external influences.